Experimental realization of multi-service RoF system using OCS-PolMux techniques - Mohamad Nor, Mohd Hafiz; Kanesan, Thavamaran; Maskuriy, Farha; Yusof, Ashaari; Abdul Fatah, Mohd Faiz Aizad; Ahmad Anas, Siti Barirah (IEEE, 2017)
Optical Carrier Suppression has been proven as an efficient way of generating high frequency optical carrier for Radio over Fiber (RoF) systems. However, previous studies show that OCS with the combination of RF and optical components can only transmit a single service in RoF system. This paper shows that two different services can be transmitted using a single wavelength through RoF system with the use of Polarization Multiplexing (PolMux) method. The combination of these two techniques enables multiservice RoF such as LTE and WiFi services to be transmitted simultaneously to the customers.